Neuroprotection Afforded by an Enriched Mediterranean-like Diet Is Modified by Exercise in a Rat Male Model of Cerebral Ischemia - Daniel Romaus-Sanjurjo; María Castañón-Apilánez; Esteban López-Arias; Antía Custodia; Cristina Martin-Martín; Alberto Ouro; Elena López-Cancio; Tomás Sobrino (MDPI AG, 2024)
Ischemic stroke is an important cause of mortality and disability worldwide. Given that current treatments do not allow a remarkably better outcome in patients after stroke, it is mandatory to seek new approaches to preventing stroke and/or complementing the current treatments or ameliorating the ischemic insult. Multiple preclinical and clinical studies highlighted the potential beneficial roles of exercise and a Mediterranean diet following a stroke. Here, we investigated the effects of a pre-stroke Mediterranean-like diet supplemented with hydroxytyrosol and with/without physical exercise on male rats undergoing transient middle cerebral artery occlusion (tMCAO). We also assessed a potential synergistic effect with physical exercise. Our findings indicated that the diet reduced infarct and edema volumes, modulated acute immune response by altering cytokine and chemokine levels, decreased oxidative stress, and improved acute functional recovery post-ischemic injury. Interestingly, while physical exercise alone improved certain outcomes compared to control animals, it did not enhance, and in some aspects even impaired, the positive effects of the Mediterranean-like diet in the short term. Overall, these data provide the first preclinical evidence that a preemptive enriched Mediterranean diet modulates cytokines/chemokines levels downwards which eventually has an important role during the acute phase following ischemic damage, likely mediating neuroprotection.